Czego może nauczyć wygnany poeta? Dydaktyczne aspekty wygnańczych utworów Owidiusza - Puk, Marlena (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2009)
This article aims to discuss some of didactic aspects in Ovid’s Tristia and Epistulae ex Ponto and to prove that the exiled poet could be also seen as a teacher. In this paper are inserted some remarks on the topical, stylistic and lingual level.

Ovid is well known from his early youthful works as a teacher, especially a teacher of love. Evidently, later he regretted what he had been teaching. One might also question whether or not the poet could teach his readers something later in life. The analysis of Tristia and Epistulae ex Ponto shows the didactic aspects of his poetry. This paper aims to discuss some of these questions. Stylistic and linguistic investigation shows that the poet uses the language of didactics, pressupposes the presence of the auditor and employs various systems of question and answer. His elegies contain fragments which sound like morals, and others contain fable like passages. Ovid gives some precepts to his friends, his family and finally to the emperor. Ovid's increasing use of aphorisms, during the period of his exile, has led scholars and researchers to believe that this is an indication of a new sententious style, and a transition from "Golden" to "Silver Age" poetry. The banished poet throughout his sufferance had also the very good lesson for himself. He can teach patience and solace. Ovid, in his last works created the myth of exile, which is complex and multidimensional, universal and timeless; he generated the exemplary model of an exiled artist’s behaviour. In this sense, the author teaches how banished poets can deal with exile and his collection was a source of exilic “topoi”. All the examples of his exilic works’ reception testify to how good a teacher he was. This reception involves themes and vocabulary as well.
What can the banished poet Ovid teach? – didactic aspects of Ovid’s exilic corp
Keywords: Ovid; exile poetry; didactic aspects; banished poet